(3GdJabjg aj TQM GdJfHjgs - (3YHO Gddg eMeO Hf YHO Gddg Hf CHi HcQ Hf CHi GdSYhO GdMKjKi GdUQOai GdQjeis; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
" (3HGH MO bGWY GdWQjb(B": (3Cbhd bGWY GdWQjb jSei HgPG GdGSe , dCfg jefY GdfGS GdeQhQ ai GdWQjb s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ef (B" (3cJGH GdCbVjI (B" (3bhdg (B: (3hjSJMH Cf jLdS eSJbHd GdbHdI Cbhd (B: (3deG Qhi GHf YHGS Cf GdfHi Udi Gddg Ydjg hSde (B: (3bGd (B( (3dcd TF TQakG ,hEf CTQa GdeLGdS eG ESJbHd Hg GdbHdI (B) s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs